Коррозионные свойства электроосажденных сплавов Со-Мо и Со-Мо-Р, полученных из полилигандного электролита - Японцева, Ю. С.; Громова, В. А. (НТУ "ХПИ", 2008)
В роботі досліджено склад і вихід за струмом електролітичних сплавів Со-Мо і Со-Мо-Р, отриманих із цитратного і полілігандного електроліту. Показано, що застосування пірофосфату, як додаткового ліганду, призводить до значного збільшення швидкості осадження сплавів і до зменшення вмісту в них молібдену, порівняно із відомим цитратним електролітом. Проведено корозійні випробування отриманих осадів і показано, що покриття мають значний корозійний опір, порядку 9,4•10³ – 1,7•10⁴ Ом.

In this work the composition and current efficiency of electrolytic alloys Co-Mo and Co-Mo-P obtained from a citrate and a polyligand citrate-pyrophosphate electrolyte have been investigated. It has been shown that the use of pyrophosphate as an additional ligand leads to a considerable increase in the deposition rate of alloys and to a decrease in the molybdenum content of them in comparison with known citrate electrolyte. Corrosion tests of the deposits obtained have been carried out, and it has been shown that coatings have a considerable corrosion resistance, 9,4•10³ – 1,7•10⁴ .
Keywords: гальванические покрытия; вольтамперометрические зависимости; защитно-декоративные покрытия; двойной сплав; тройной сплав; омическое сопротивление